Analysis of Capital Funding: Risks, Scale, and Feasibility Perspective - Rosita, R.; Rum, Muh.; Rustam, Andi (Manunggal Halim Jaya, 2024)
This study aims to assess the impact of financial risk and a viable business scale on the volume of capital funding for SMEs at PT PNM Mekaar Takalar. The research provides valuable insights and knowledge for readers to better understand financial risks, business scale, feasibility, and capital funding. Specifically, the objective is to examine the relationship between financial risk, business scale, and financial feasibility on the volume of capital funding for SME customers at PT PNM (Persero) Mekaar Takalar Unit. The research poses a key question: Does the risk of a viable business scale have a significant positive impact on the volume of capital funding for SMEs at PT PNM Mekaar Takalar? This study employs an associative quantitative approach, which examines the relationship between two or more variables, as defined by Sugiyono (2013). The research explores three main variables: financial risk (X1), business scale (X2), and financial feasibility (X3), and their influence on the capital funding volume of PT PNM Mekaar Takalar's SME customers. The study was conducted at the PNM Mekaar office in the Takalar Area over a two-month period. The population consisted of all 50 employees of PT PNM Mekaar Takalar, and the research employed a saturated sampling method, where the sample size equaled the population, resulting in a total sample of 50 employees. The findings revealed that financial risk had no significant impact on the volume of business capital funding, likely due to insufficient risk identification and categorization in lending processes. In contrast, business scale had a significant effect on capital funding, as respondents prioritized sales volume. However, financial feasibility did not significantly influence the capital funding volume, as respondents tended to prioritize income over other factors.